Safe lists for medications in pregnancy: inadequate evidence base and inconsistent guidance from Web‐based information, 2011. (29th January 2013) - Peters, Stacey L.; Lind, Jennifer N.; Humphrey, Jasmine R.; Friedman, Jan M.; Honein, Margaret A.; Tassinari, Melissa S.; Moore, Cynthia A.; Mathis, Lisa L.; Broussard, Cheryl S.
ABSTRACT Purpose Medication use during pregnancy is common and increasing. Women are also increasingly getting healthcare information from sources other than their physicians. Methods This report summarizes an environmental scan that identified 25 active Internet sites that list medications reported to be safe for use in pregnancy and highlights the inadequate evidence base and inconsistent guidance provided by these sites. Results These lists included 245 different products, of which 103 unique components had been previously evaluated in terms of fetal risk by the Teratogen Information System (TERIS), a resource that assesses risk of birth defects after exposure under usual conditions by consensus of clinical teratology experts. For 43 (42%) of the 103 components that were listed as 'safe' on one or more of the Internet sites surveyed, the TERIS experts were unable to determine the fetal risk based on published scientific literature. For 40 (93%) of these 43, either no data were available to assess human fetal risk or the available data were limited. Conclusions Women who see a medication on one of these 'safe' lists would be led to believe that there is no increased risk of birth defects resulting from exposure. Thus, women are being reassured that fetal exposure to these medications is safe even though a sufficient evidence base to determine the relative safety or risk does not exist. Copyright © 2013 John Wiley & Sons, Ltd.